Finite fractal dimension of pullback attractors for semilinear heat equation with delay in some domain with moving boundary. (December 2022) - López-Lázaro, Heraclio; Nascimento, Marcelo J.D.; Rubio, Obidio
Abstract: In this article we study a semilinear mathematical model with delay term for thermal conduction problems defined on a one-dimensional moving boundary domain. The goals of this work are to prove existence, regularity, and finite fractal dimension of the pullback attractors on tempered universes that depends on a non-increasing function η : R → ( 0, + ∞ ) .